(untitled) (Physical Education, Health and Social Sciences, 2026)
The purpose of this study is to examine how technology and parental status affect Pakistani children’s educational attainment. The data used in this study is district wise data and has been taken from Pakistan Social and Living Standard Measurement (PSLM 2019-20). Our dependent variable is children’s years of schooling, for parental prestige and technology we have constructed an index using three variables: mother’s education level, father’s income level, and the wealth of the household. By employing Ordinary Least Square (OLS), we found that parental prestige and technology played important role in all over Pakistan both in rural and urban areas. Moreover, we analyzed males and females separately, male is always in advantageous as compared to females in terms of educational attainment, this can lead to male dominant society of Pakistan. Furthermore, cohort-wise analysis confirmed the fact that parental prestige and technology are important factors affecting educational attainment positively and significantly regardless of any specific time.